PENGURUSAN ZAKAT: SATU ANALISIS DARI PERSPEKTIF AL-QURAN DAN AL-SUNNAH - Buang, Ahmad Hidayat (Jurnal Syariah, 2019)
Zakat is paid to the poor by the rich in Muslim society as a religious due. In the Prophet Muhammad’s time, the collection and distribution ofZakat was managed by the Prophet himself with the help some of his agents called su ’at. The practice and method of zakat’s collection and distribution in Muslim society hitheno has its high and low tide with the progress of Muslim society. At its lowest ebb zakat is considered merely as a personal religious obligation by the rich to the poor. With the rise of Islamic awareness of the Muslim society of lately, zakat appears to attract some serious discussion among scholars on its role and junction in the Muslim society. One of the aspect discussed is the problem of zakat’s management which is said by some quarters to be unsatisfactory from the view point of modem method of tax collection and distribution. This anicle however is not going to discuss the whole issue, it will only analyze some provisions from the sources of Islamic law especially the Qur’ an and the Sunnah on how the collection of zakat in panicular can be best managed.